Moral Competence as a Positive Youth Development Construct: A Conceptual Review - Hing Keung Ma (The Scientific World Journal)
Moral competence refers to the affective orientation to perform altruistic behaviors and the ability to judge moral issues logically. A five-stage theory of moral development is proposed. Both western and Chinese perspectives are incorporated in the elaboration of the characteristics of each stage. A brief review of the antecedents of moral competence is presented. The relationship between moral competence and adolescent developmental outcomes is also discussed. Some practical ways to promote moral competence are suggested. School-based programs may be effective in the promotion of moral competence provided it is based on all-round or whole-person development and the length of the program should be sufficiently long.